Pengaruh Jarak Penghamparan Terhadap Perubahan Suhu Campuran - Rini, Alvio; Putra, Sasana; Pratomo, Priyo (Universitas Lampung, 2018)
Pavement is widely used in Indonesia is a mixture of laston, in its implementation temperature is very influential on the overlay process, temperature also affects the density process. The further the distance of AMP (Asphalt Mixing Plant) to the overlay location, the greater the decrease in temperature, and the decrease in density results. So it is necessary to do a study about effect of spread distance to mixed temperature change. The mixture used is Asphalt Concrete-Wearing Course from Asphalt Mixing Plant produced by PT Manggung Polah Raya for location on Sultan Agung Street, Bandar Lampung, Lampung and PT. Rindang Tiga Satu Pratama for the location of Teuku Cik Ditiro Street, Bandar Lampung, Lampung. From the analysis results of 2 AMP (Asphalt Mixing Plant), PT. Manggung Polah Raya and PT. Rindang Tiga Satu Pratama using logarithmic regression analysis, obtained that the distance and the Δtemperature are 0,9832 and 0,7366. The result of Δtemperature and Δdensity are 0,0568 and 0,0688 and the result of distance logarithmic regression analysis and Δdensity are 0,0326 dan 0,005. The result of the combined logarithmic regression analysis of PT. Manggung Polah Raya and PT. Rindang Tiga Satu Pratama between distance and Δtemperature is 0,7829 and 0,0005 for Δtemperature and Δdensity. Factor that influence the decrease of the temperature is the haulage process of the transport mixture. If the temperature decrease, then the result of the density are not maximal. Keyword: Mixture Temperature Change, Distance, Density.